2001
DOI: 10.1074/jbc.m103473200
|View full text |Cite
|
Sign up to set email alerts
|

Manic Fringe and Lunatic Fringe Modify Different Sites of the Notch2 Extracellular Region, Resulting in Different Signaling Modulation

Abstract: Three mammalian fringe proteins are implicated in controlling Notch activation by Delta/Serrate/Lag2 ligands during tissue boundary formation. It was proved recently that they are glycosyltransferases that initiate elongation of O-linked fucose residues attached to epidermal growth factor-like sequence repeats in the extracellular domain of Notch molecules. Here we demonstrate the existence of functional diversity among the mammalian fringe proteins. Although both manic fringe (mFng) and lunatic fringe (lFng) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
3
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 39 publications
8
92
3
1
Order By: Relevance
“…Notch1 has Ͼ20 EGF repeats that contain a consensus sequence for O-fucosylation and most may be modified by Fringe (7). It is known that the action of Fringe in transferring GlcNAc to EGF-O-fucose causes changes in soluble ligand binding to Notch receptors (5,(13)(14)(15). We have shown that Lec13 mutant cells with low fucose in glycoproteins exhibit reduced Notch signaling for both Jagged1 and Delta1 ligands (refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch1 has Ͼ20 EGF repeats that contain a consensus sequence for O-fucosylation and most may be modified by Fringe (7). It is known that the action of Fringe in transferring GlcNAc to EGF-O-fucose causes changes in soluble ligand binding to Notch receptors (5,(13)(14)(15). We have shown that Lec13 mutant cells with low fucose in glycoproteins exhibit reduced Notch signaling for both Jagged1 and Delta1 ligands (refs.…”
Section: Discussionmentioning
confidence: 99%
“…It is found on urokinase-type plasminogen activator (uPA) (8), on Notch receptors and their ligands (6,9), on Cripto (10,11), and on other proteins, including blood clotting factors. O-Fucose is required for signaling by uPA through the uPA receptor (12), for Fringe modulation of Notch receptor signaling in Drosophila (4,5) and in coculture assays (4,(13)(14)(15)(16), and for Cripto to mediate Nodal signaling (10,11).…”
mentioning
confidence: 99%
“…In general, Lunatic Fringe (Lfng) and Manic Fringe (Mfng) inhibit Jagged1-induced Notch signaling and increase Delta1-induced Notch signaling. However, differences between the effects of Lfng and Mfng on Notch2 signaling have been observed [18], and Radical Fringe (Rfng) overexpression in NIH3T3 cells enhances both Delta1-and Jagged1-induced Notch signaling [19]. Lfng, Mfng and Rfng differ in in vitro specific activity [20], and their activities may not be equivalent in different cell types.…”
Section: Notch Receptors In the Absence Of Fringementioning
confidence: 99%
“…Many of the O-fucose monosaccharides on Notch can be extended with GlcNAc by a single Fringe enzyme in Drosophila and by any of three Fringe enzymes-Lunatic fringe (Lfng), Manic fringe (Mfng), or Radical fringe (Rfng) in mammalian organisms (24), each of which affects Notch activity in slightly different ways (17,(25)(26)(27). The simplest case appears in flies, where Fringe modification has a positive effect on Delta-mediated signaling and a negative effect on Serrate-mediated signaling.…”
mentioning
confidence: 99%